Autorregulación en el mercado de valores: costos y beneficios y la importancia de cuantificarlos (2012)
This paper explains the benefits and costs of self-regulation in the stock market, as well as the importance of conducting costbenefit analysis of the implementation of this model. The main advantage of the model independent Organization Self-Regulation on the model of government is the cost of information. And the main benefits of an independent Organization Self-Regulation, is precisely this experience that can be embodied in legislation more adjusted to reality. Additionally in this paper I describe the impact of the financial crisis the 2008 in the financial market and the opportunities to Self-Regulation and its challenges.